The Relationship between Nutritional Knowledge with Nutrient Intake and Adherence to the Consumption of Blood-Added Tablets in Adolescent Girls at SMA Islam SHAFTA Surabaya - Septalia Puji Rahmawati; Ani Intiyati; Nur Hatijah; Inne Soesanti (Politeknik Kesehatan Kemenkes Surabaya, 2023)
ABSTRACT Anemia is a nutritional problem of adolescents in Indonesia that occurs due to iron deficiency. The purpose of the study was to analyze the relationship of nutritional knowledge with nutrient intake and adherence to the consumption of blood-added tablets in adolescent girls at SMA Islam SHAFTA Surabaya. This type of research is analytical descriptive research with a cross sectional design. Large sample of 45 respondents. Data collection with interviews and SQ-FFQ. Furthermore, it was analyzed with the spearman correlation test. The results of the analysis indicate that the majority of respondents' characteristics are aged 16-18 years (68.9%). Good nutrition knowledge 35 respondents (77.8%). Protein intake 32 respondents (71.1%) severe deficit, iron intake 36 respondents (80%) deficient and 41 respondents (91.1%) non-compliant. There was no relationship between nutritional knowledge with protein intake (p value = 0.428), nutritional knowledge with iron intake (p value = 0.685), and nutritional knowledge with adherence to blood added tablet consumption (p value = 0.231). There is no relationship between variables and it is necessary to collaborate on independent blood added tablets and health counseling at school.